High-tech gazelle firms at various stages of evolution: performance and distinctive features; Journal of Economic Studies; Vol. XX, iss. X - Spitsin V. V. Vladislav Vladimirovich; Vukovic D. Darko; Mikhalchuk A. A. Aleksandr Alexandrovich; Spitsina (Spitsyna) L. Yu. Lubov Yurievna; Novoseltseva D. A. Darjya Andreevna (2022, 2022)
Title screen